2020
DOI: 10.1161/hypertensionaha.119.14062
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Chaperone Calmegin Is Upregulated in Aldosterone-Producing Adenoma and Associates With Aldosterone Production

Abstract: The endoplasmic reticulum (ER) plays a pivotal role in syntheses of proteins and steroid hormones and regulation of intracellular Ca 2+ level. We aimed to investigate ER-associated genes in aldosterone-producing adenomas (APAs) and clarify their effect on aldosterone production. Microarray analysis targeting 288 ER-associated genes was conducted using nonfunctioning adrenocortical adenomas (n=5) and APAs (n=19). Immunohistochemistry and quantitative polymerase chain reaction analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Depolarization activates voltage-gated Ca 2+ channels and intracellular calcium signaling and promotes the transcription of aldosterone synthase ( CYP11B2 ), resulting in overproduction of aldosterone ( Figure 1 ). Furthermore, some key molecules such as VSNL1, CALN1, GSTA1, NPNT, and CLGN have been detected in APA, and their functions in aldosterone production have been elucidated [ 14 , 15 , 16 , 17 , 18 ]. Epigenetic regulation of CYP11B2 has also been indicated in APA [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depolarization activates voltage-gated Ca 2+ channels and intracellular calcium signaling and promotes the transcription of aldosterone synthase ( CYP11B2 ), resulting in overproduction of aldosterone ( Figure 1 ). Furthermore, some key molecules such as VSNL1, CALN1, GSTA1, NPNT, and CLGN have been detected in APA, and their functions in aldosterone production have been elucidated [ 14 , 15 , 16 , 17 , 18 ]. Epigenetic regulation of CYP11B2 has also been indicated in APA [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Entire intracellular mechanisms of aldosterone production are still complex. In addition, recent basic studies suggested that mRNA translation and translation via miRNA also participate aldosterone regulation in APA [19,[45][46][47], however these have not been fully elucidated. Significant more work including basic studies on the regulation of aldosterone biosynthesis will be necessary for the development of medical therapies for primary aldosteronism and aldosterone-producing adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…CLGN, calmegin, is the highest expressed genes among ER related genes in APA in comparison to NFA by transcriptome analysis [19]. CLGN over-expressing adrenal cells increased CYP11B2 protein levels and aldosterone production, but not CYP11B2 transcription [19].…”
Section: Functional Analysis Based On Transcriptome Analysis In Apamentioning
confidence: 99%
See 2 more Smart Citations